GEOGRAFI DIALEK BAHASA MENTAWAI - Rita Novita (Widyariset, 2009)
This research aims to portray the geography dialect in Mentawai Regency. The dialects in Mentawai Island are observed using dialectology approach. There were three dialects, namely: north Siberut dialect, South Siberut dialect, and Sipora-Sikakap dialect. Then, the sub-dialects found were Sipora sub-dialect and Sikakap sub-dialect. There are dialect and subdialect which are clearly seen in the map of dialect geography of Mentawai Regency.